A power perspective on knowledge transfer in internal succession of small family businesses. (3rd September 2017) - Muskat, Birgit; Zehrer, Anita
Abstract : The aim of this paper is to apply a power perspective to knowledge transfer in internal succession processes of small family businesses. We argue that knowledge is a source of power. Distilling existing literature on small family businesses, knowledge transfer and power theory, we focus on the role of owner-manager and successor in internal succession. Propositions are formulated, theorizing the influence of (1) expert power, (2) decision-making power, (3) trust, (4) rivalry, and (5) capabilities. First, we conclude, familiness and high levels of trust in small family businesses influence power relationships between successor and predecessor positively. Second, the existence of high power imbalances within familiness can slow progress in knowledge transfer in succession, and particularly negatively impact on tacit knowledge transfer from one generation to the next.